2020
DOI: 10.48550/arxiv.2003.11754
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Thermodynamics and P-v criticality of Bardeen-AdS Black Hole in 4-D Einstein-Gauss-Bonnet Gravity

Dharm Veer Singh,
Sanjay Siwach

Abstract: We consider the Gauss-Bonnet corrected Bardeen black hole solution in 4D AdS space-time. The solution is obtained by the limiting procedure adopted by Glavan and Lin in 4D Einstein-Gauss-Bonnet gravity. The general form of first law of black hole thermodynamics is utilized to calculate various thermodynamics variables. The solution exhibit P-v criticality and belong to the universality class of van-der Waals fluid. The effect of Gauss-Bonnet coupling is investigated on critical parameters and inversion tempera… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
24
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 33 publications
(42 reference statements)
0
24
0
Order By: Relevance
“…Interestingly, the solution of the same form has been presented in the conformal anomaly inspired gravity [39]. Along this line, the Einstein-Gauss-Bonnet gravity in the 4D spacetime has been explored extensively on various aspects, including the exact solutions [40][41][42][43][44][45][46][47][48], the quasinormal modes and stability [49][50][51][52][53][54][55][56][57][58], the observable shadows [59][60][61][62][63][64], the geodesics and gravitational lensing [65][66][67][68][69], the thermodynamics and cosmic censorship conjecture [70][71][72][73][74][75][76][77][78],…”
Section: Introductionmentioning
confidence: 89%
“…Interestingly, the solution of the same form has been presented in the conformal anomaly inspired gravity [39]. Along this line, the Einstein-Gauss-Bonnet gravity in the 4D spacetime has been explored extensively on various aspects, including the exact solutions [40][41][42][43][44][45][46][47][48], the quasinormal modes and stability [49][50][51][52][53][54][55][56][57][58], the observable shadows [59][60][61][62][63][64], the geodesics and gravitational lensing [65][66][67][68][69], the thermodynamics and cosmic censorship conjecture [70][71][72][73][74][75][76][77][78],…”
Section: Introductionmentioning
confidence: 89%
“…Quasinormal modes of bosonic fields [49] and fermionic fields [50] of these black hole have been investigated, and it is found that for the bosonic fields the damping rate is more sensitive than the real part of quasinormal modes by changing of the GB coupling constant α, while for the fermionic fields the damping rate usually decreases and the real part of the quasinormal modes increases with the increase of α. Konoplya and Zhidenko discussed the stability [51] of spherically symmetric black holes in the novel EGB gravity. Moreover, other topics in this new theory including the charged black holes in AdS spaces [52], the rotating black holes [53,54], radiating black holes [55], the structure of relativistic stars [56], the thermodynamics of the black holes [57][58][59][60] and the accretion disk around the black hole [61] have also been studied.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, the novel 4D EGB theory has attracted extensive attention recently, ranging from applications of black hole physics and in investigating their properties [3][4][5][6][7][8], rotating black holes [9,10], black holes coupled with magnetic charge [11][12][13][14], Born-Infeld black holes [15], relativistic stars [16,17], gravitational lensing [18,19], radiation and accretion phenomena [20,21], stability issues [22][23][24], quasi-normal modes [25,26], black hole shadows [27][28][29], to thermodynamics and phase transitions [30][31][32][33][34], amongst other topics. Nevertheless, a number of questions [35][36][37][38][39][40][41][42] have been raised on the adopted approaches in [1,43], and some remedies have also been suggested to overcome these difficulties [39,[44][45]…”
Section: Introductionmentioning
confidence: 99%